Achieving loyalty for sharing economy platforms: an expectation–confirmation perspective. Issue 7 (2nd June 2020) - Jia, Fu; Li, Dun; Liu, Guoquan; Sun, Hui; Hernandez, Jorge E.
Abstract : Purpose: This study explores how sharing platforms achieve platform loyalty through various operation management strategies. Design/methodology/approach: A multiple case study method has been conducted in two Chinese sharing economy industries: ride- and bike-sharing. Data were collected through 30 semi-structured interviews with managers from four platform companies (DiDi, Uber China, ofo and Mobike). Individual case studies were developed from the triangulation of all existing data. Concurrent with the development of these individual case studies was a cross-case analysis. Emerging patterns have been identified and compared to previous findings in the literature to build upon and modify the existing knowledge base and to formulate a series of propositions. Findings: Platform asset characteristics and mergers and acquisitions affect supply network readiness and operational capacity, respectively, and this effect would consequently contribute to achieving platform loyalty through user satisfaction. Moreover, externality, as a moderator, may influence the strength of the relationship between satisfaction and platform loyalty. Practical implications: The proposed theoretical model provides an overarching framework for sharing platform companies to design and operate their businesses while carefully examining the situations, contexts and actions of users and other stakeholders and choosing an appropriate strategic mechanism to drive platform growth. Originality/value: This study is one of the first to empirically explain how firms in a sharing economy sector could gain platform loyalty by adopting an expectation–confirmation theory perspective.